Luncheon given for Admiral Richard E. Byrd, May 29, 1935 - Byrd, Richard Evelyn, 1888-1957 (Byrd Polar Research Center Archival Program, 1935)
The media can be accessed here: http://streaming.osu.edu/knowledgebank/byrd/8891-8895.mp3 Thomas J. Watson of IBM discusses the importance of pioneer work and the personality traits required to follow through ideas. Watson thanks Byrd and speaks of the thrill when hearing Byrd broadcast over radio from Little America. Watson assures Byrd of future cooperation of IBM, the importance of Little America, and invites Byrd to speak. Byrd contrasts North and South Poles, discussing animal life and temperature, as well as living under the ice and snow, testing thickness of ice, and concludes speech with comments on how he has enjoyed the luncheon. The recording ends with Watson’s praise of Byrd. Digital preservation funded by the Kane Lodge Foundation, Inc., New York, New York.